2010
DOI: 10.1007/s00467-009-1402-8
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus nephrotoxicity: beware of the association of diarrhea, drug interaction and pharmacogenetics

Abstract: Tacrolimus is known to potentially lead to adverse events in recipients with diarrhoea and/or calcium channel blocker (CCB) co-administration. We report a renal transplant recipient who suffered from severe nephrotoxicity related to a toxic tacrolimus trough concentration in both conditions, diarrhoea and CCB co-administration, and with genotyped CYP3A system and P-glycoprotein (P-gp) polymorphisms. To our knowledge, this is the first case to be investigated for such polymorphisms. Clinicians should be reminde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…In renal transplant recipients with hypertension, CsA metabolism was shown not to interfere with AML (Toupance et al, 1994), but another two studies (Katoh et al, 2000;Kuzuya et al, 2003) showed that AML increased CsA concentration. At present, only one clinical case study (Leroy et al, 2010) suggested that AML elevated the concentration of TAC. A 14-year-old Caucasian male underwent renal transplantation was given AML as an antihypertensive drug with an increasing dose from 10 to 30 mg/d followed by a reduction by one-third of the TAC dose: the trough concentration of TAC was 27.2-38.8 mg/L.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In renal transplant recipients with hypertension, CsA metabolism was shown not to interfere with AML (Toupance et al, 1994), but another two studies (Katoh et al, 2000;Kuzuya et al, 2003) showed that AML increased CsA concentration. At present, only one clinical case study (Leroy et al, 2010) suggested that AML elevated the concentration of TAC. A 14-year-old Caucasian male underwent renal transplantation was given AML as an antihypertensive drug with an increasing dose from 10 to 30 mg/d followed by a reduction by one-third of the TAC dose: the trough concentration of TAC was 27.2-38.8 mg/L.…”
Section: Discussionmentioning
confidence: 95%
“…AML is an inhibitor of CYP3A2 in rats (Drobitch et al, 1997) and a substrate of P-gp (Katoh et al, 2000;Kuzuya et al, 2003). Only one clinical case report (Leroy et al, 2010) has suggested that AML might increase the TAC concentration. However, in vivo studies in rats or humans focusing on the interactions between AML and TAC warrant investigation.…”
Section: Introductionmentioning
confidence: 95%
“…An example of a considerable drug-related adverse event due to changes in metabolizing enzymes and efflux transporters involves a child with confirmed CYP3A deficiency that had been on stable doses of tacrolimus for 9 years [68]. The bioavailability and pharmacokinetics of tacrolimus are highly dependent on intestinal CYP3A and P-gp systems.…”
Section: Reduced Cyp3a Enzymes and Metabolismmentioning
confidence: 99%
“…Severe diarrhea (more than three loose stools daily) may result in an elevated tacrolimus trough level and subsequent drug toxicity 118,119 . Tacrolimus is metabolized by cytochrome P450 (CYP) 3A4 and 3A5 isoforms, which are present at high levels in enterocytes.…”
Section: Calcineurin Inhibitorsmentioning
confidence: 99%